Maneuvering Target Tracking with Multi‐Model Based on the Adaptive Structure. Issue 6 (21st February 2022) - Guo, Qiang; Teng, Long
Abstract : In the "snake" maneuver tracking of anti‐ship missiles, the traditional interactive multi‐model algorithm has poor tracking accuracy and the computational complexity of the improved algorithm is large. An adaptive structure multi‐model (ASMM) algorithm is proposed to solve this problem. The multi‐model tracking algorithm is improved from two aspects: tracking accuracy and computational complexity. First, the fuzzy control idea is introduced to speed up the update of the model probability, which improves the convergence speed and tracking accuracy of the interacting multiple model (IMM) algorithm. Next, a tracking model with an adaptive structure is proposed, which can adjust the tracking model adaptively according to the motion form of the target, thereby reducing the calculation redundancy. The simulation experiment shows that the proposed algorithm has better tracking accuracy than the traditional multi‐model algorithm while maintaining the approximate computational complexity, and has smaller computational complexity than the traditional improved algorithm while maintaining the approximate tracking accuracy. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.